Effect of GnRH Administered 7 Days after Insemination on Serum Progesterone, Luteinizing Hormone and Duration Estrous Cycle with Pregnancy Rates in Heifers - Kaygusuzoglu, Erdal; Yildiz, Hamit; Kaya, Mehmet; Cenesiz, Metin (Medwell Online, 2010)
Serum Progesterone (P4), Luteinizing Hormone (LH) concentrations, estrous cycle lenght ve pregnancy rates were determined in Gonadotropin Releasing Hormone (GnRH; 10.5 mu g synthetic gonatotrophin releasing hormone agonist, receptal) administered heifers on day 7 after insemination (n = 9) compared to control heifers (n = 5). All heifers oestrous cycle were synchronised by intramuscular administration of prostaglandin F(2) alpha (its analog, cloprostenol) twice at 11 days interval. Estrous exhibited heifers were mated naturally. Blood samples were collected every two days from all animals. Serum progesteron and LH concentrations were measured by ELISA method. GnRH administration significantly increased serum LH concentration which reached peak level 2nd h after treatment. However, serum progesterone concentration was not affected. There were no differences in mean progesterone concentrations on days 7-24 after insemination between GnRH administered and control pregnant heifers. However, in non pregnant animals, progesteron concentrations of treated group were significantly lower than control group on 16th day (p < 0.05). Pregnancy diagnosis was made by B-mode ulfrasonography between the 30 and 35th days following insemination. Pregnancy was determined in 5 animals in treated group and in 2 animals in control group. Duration of the estrous cycle in the non-pregnant animals was not affected by the treatment (control, 20.6 +/- 0.96 days; treated, 19.5 +/- 0.93 days). In conclusion, this study supports the use of GnRH after insemination of 7 day as a method for enhancing pregnancy rates in heifers.
Keywords: Pregnancy; heifer; progesterone; LH; GnRH; oestrous cycle length